2006
DOI: 10.1001/jama.295.20.2366
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Colorectal Cancer Following a Negative Colonoscopy Examination

Abstract: The risk of developing colorectal cancer remains decreased for more than 10 years following the performance of a negative colonoscopy. There is a need to improve the early detection rate of right-sided colorectal neoplasia in usual clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
208
2
28

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(252 citation statements)
references
References 35 publications
(36 reference statements)
11
208
2
28
Order By: Relevance
“…The optimal interval for colonoscopy screening has been assessed in a cohort study and a case-control study. The cohort study found that CRC incidence in a population with negative colonoscopy was 31% lower than general population rates and remained reduced beyond 10 years after the negative colonoscopy (Singh et al, 2006). Similar results were obtained in the case-control study (Brenner et al, 2006) where the reduction of risk of CRC was 74 % and persisted up to 20 years.…”
Section: Evidence For Effectiveness Of Colonoscopy Screeningsupporting
confidence: 69%
“…The optimal interval for colonoscopy screening has been assessed in a cohort study and a case-control study. The cohort study found that CRC incidence in a population with negative colonoscopy was 31% lower than general population rates and remained reduced beyond 10 years after the negative colonoscopy (Singh et al, 2006). Similar results were obtained in the case-control study (Brenner et al, 2006) where the reduction of risk of CRC was 74 % and persisted up to 20 years.…”
Section: Evidence For Effectiveness Of Colonoscopy Screeningsupporting
confidence: 69%
“…In our study, this proportion was 41.1% and increased over time, compared with 9.8% in the Canadian study. The persisting (albeit strongly reduced) differences in risk reduction for right-and left-sided cancer might reflect a remaining higher percentage of missed adenomas in the right colon (12,13,31) or differences in the biology of right-and left-sided cancer (31)(32)(33)(34). The age gradient with less pronounced risk reduction of right-sided cancer at younger ages might be a possible indication of the importance of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that the "protective effect" of a negative SC in terms of decreased CRC mortality lasts for more than 10 years [33][34][35][36][37] . Based on estimates from this literature, we reduced the CRC mortality rate by 50% and replicated the analysis to estimate how these patients would benefit from SC.…”
Section: Estimating the Colorectal Cancer-attributable Risk Of Deathmentioning
confidence: 99%